Communal Coping in Couples With Health Problems - Rentscher, Kelly E. (Frontiers in Psychology, 2019)
Prior to the 1990s, the predominant view of stress and coping defined stress as occurring when an individual perceives a situation as a challenge, threat, or loss and evaluates her capacity to respond based on her available resources. As an expansion of this intrapersonal perspective, the last twenty years have seen the emergence of two prominent interpersonal perspectives on stress and coping that account for the importance of social relationships in the coping process: the Systemic Transactional Model of dyadic coping and communal coping. In this article, I outline these two perspectives and highlight their points of convergence and divergence. I propose that one difference between the models is that communal coping involves an explicit focus on a communal orientation or shared appraisal process, in which relationship partners view a problem or stressor as “ours” rather than “yours” or “mine”. I review existing methods for assessing communal coping (e.g., self-report, language use, behavioral observation) across laboratory, intervention, and real-world settings and summarize empirical evidence for the prognostic significance of communal coping for relationship and health functioning. I propose the utility of incorporating measurement of communal orientation into future research on dyadic coping with stress, because of its potential to impact health through its influence on primary and secondary stress appraisal processes and physiological stress response systems. Finally, I outline biological and behavioral pathways through which communal coping may influence health as directions for future research.